ANALISIS KARAKTERISTIK ALIRAN FLUIDA FANCENTRIFUGAL DENGAN VARIASI JUMLAH BLADEMENGGUNAKAN PENDEKATAN COMPUTATIONALFLUID DYNAMICS - Muhammad Arief Alfarizi, (2021)
Centrifugal fans are machines that circulate air and can be used in rough operations. The fluid flow that crosses the centrifugal fan will be compressed so that the pressure will increase. The backward inclined type centrifugal fan has a fairly high efficiency value so that the pressure generated by the backward inclined type centrifugal fan can be influenced by several factors, one of which is the number of impeller blades. The impeller blade is an important geometry in the fan because it can affect the work of the centrifugal fan. This study aims to determine the characteristics of the fluid flow through the backward inclined type centrifugal fan and the effect of the number of blades on the performance of the centrifugal fan. This method can be done by numerical simulation and volume method by varying the number of 10, 12 and 14 blades with shaft rotation speed of 1800, 1900 and 2000 rpm. The mesh value used has been done with a mesh independence test. The simulation results obtained after iteration can be said to have reached the convergence value. The simulation results show that by varying the number of blades on the centrifugal impeller fan with the number of blades 10 having the largest velocity outlet value and the number of blades 14 having the largest pressure outlet value. the smaller the outlet velocity value and the greater the outlet pressure value. the highest performance and efficiency was obtained at the number of blades 14 with a rotation speed of 2000 rpm, which was 155,285 watt and 23.6%